Plan de negocio para la Distribuidora Smart Glass - Rodríguez Vite, Jesús Adrián (2024)
The research aimed to design a business plan for Distribuidora Smart Glass in Santo Domingo de los Colorados, a company dedicated to the distribution of aluminum profiles and glass products, as support to strengthen various aspects of its operations in different areas. The execution was divided into three phases. In the first phase, a market study was conducted, starting with a visit to the company to gather information through an interview with the owner and a survey applied to local artisans. From this, an analysis of supply and demand was carried out, along with the situational diagnosis using PESTEL, Porter’s Five Forces, and SWOT analysis, which provided insights into the acceptance of the business in the current market. The second phase focused on the technical-operational study, defining the equipment, materials, merchandise, and other supplies needed for the company's operation, each detailed with their respective costs, as well as the description of the infrastructure, organizational structure, and legal aspects. In the third phase, an economic-financial study was developed to assess the project's economic viability, yielding a positive outcome for its continuation. This was achieved through the application of financial indicators, along with a description of costs, revenues, and expenses, with projections for the first five years from the start, considering a 2% increase in profit from the second year onwards.